Analisis Permasalahan Pembelajaran Daring Selama Pandemi Covid 19 dan Solusinya - Joko Suprapmanto; Utomo (Nusa Putra University, 2021)
This article aims to determine the role that parents play in their child's growth and development during the covid 19 pandemic. The research method used is a case study through interviews. The analysis technique in this research is thematic analysis. The research subjects used were 34 housewives from various professions. The research was conducted in the village of Cibolang Kaler, Sukabumi, West Java. The results showed that the problems faced by parents were limited devices for online learning, unstable internet connection, busy parents, information that did not arrive, children's boredom during online learning. The solutions that can be applied to overcome these problems are providing adequate facilities and infrastructure, increasing understanding of the role of parents in the growth and development of children, needing innovative learning models for online learning, schools implementing face-to-face learning and vaccination immediately.